Successful Management of Dry Socket with Alveogyl Following Posterior Mandibular Tooth Root Extraction: A Case Report - Arsheilla Ika Maulida; Kusumastiwi, Rr. Pipiet Okti (Crown: Journal of Dentistry and Health Research, 2024)
Introduction: Dry socket, or alveolar osteitis (AO), is a prevalent post-extraction complication characterized by intense pain and delayed healing. The etiology is multifactorial, often linked to trauma, infection, and lifestyle factors. Alveogyl, a medicated dressing containing iodoform, butamben, and eugenol, is commonly employed in dry socket management due to its analgesic, antiseptic, and healing properties. This case report presents the successful treatment of dry socket with Alveogyl following the extraction of retained mandibular third molar roots. Case presentation: A 22-year-old female patient presented with severe, radiating pain four days after the extraction of retained mandibular third molar roots. Clinical examination revealed an open socket with exposed bone and localized inflammation, indicative of dry socket. The patient's medical history was unremarkable, and she denied any contributing factors such as smoking or oral contraceptive use. The socket was irrigated with saline, and Alveogyl dressing was applied. Conclusion: The patient reported complete pain resolution and demonstrated significant healing at the one-week follow-up. This case underscores the efficacy of Alveogyl in managing dry socket, providing pain relief, and promoting healing. The prompt diagnosis and treatment of dry socket are crucial in mitigating patient discomfort and ensuring optimal healing outcomes. The use of Alveogyl as part of a comprehensive treatment approach can contribute to successful dry socket management.